PEMANFAATAN MEDIA SOSIAL DALAM PEMBELAJARAN MATEMATIKA PADA KELAS 6 SDN 03 BAWU BATEALIT JEPARA DI MASA PANDEMI - Khofianida, Eliya (LPPM Universitas Bina Bangsa, 2024)
The COVID-19 pandemic has had a major impact on education. Educators must ensure that teaching and learning activities continue, even though students are at home. As a solution, educators are required to design learning media as innovations by utilizing online media. The learning system is implemented through a personal mobile device or laptop that is connected to an internet network connection. The world of education today lives in the world of media, where learning activities have moved towards reducing the delivery system of teaching materials with direct methods and being replaced by the use of learning media. Moreover, in learning activities that emphasize competencies related to process skills, the role of learning media is needed. Media as an integral part of learning, this component needs to get the attention of teachers. The importance of media in facilitating students (learners), the presentation is adjusted to the set learning objectives. Educators can do learning together at the same time using groups on social media such as whatsapp (WA), Telegram, Instagram, zoom applications or other media as a medium for learning mathematics. Thus, educators can ensure that students take part in learning at the same time, even though in different places.